Explanation points : publishing in rhetoric and composition - Gallagher, John R., 1983-; DeVoss, Dànielle Nicole (Utah State University Press, 2019)
"A curated archive of disciplinary knowledge and best practices for publishing in rhetoric and composition. Covering a variety of topics in an approachable, conversational tone, that demonstrates how writing faculty from diverse sets of career trajectories and types of institutions can research and produce scholarship"--Provided by publisher"--